Urgensi Mempelajari Tarikh Tasyri' dalam Memahami Hukum Islam secara Komprehensif - Andika Darmawan; Dalail Jalal Ikhrom; Galih Satrio Negoro; Umar Al Faruq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
A comprehensive understanding of Islamic law cannot be separated from the historical context of its formation, known as the Tarikh Tasyri'. This research aims to examine the urgency of studying the Tarikh Tasyri' in order to understand Islamic law completely and contextually. The method used is a literature study with a qualitative approach through content analysis of various primary and secondary sources. The research results show that without understanding the historical background of a law, the risk of distortion of meaning and inappropriate application is very high. Tarikh Tasyri' provides an important methodological framework for understanding the dynamics of law formation, and is the basis for modern ijtihad in responding to the challenges of the times. The implications of this research suggest the need to strengthen the teaching of Tarikh Tasyri' in the Islamic education curriculum and its application in contemporary legal practice and fatwas.